Ultrastructures of fat body cell and follicle prior to and during the vitellogenesis of Pteromalus puparum - LÜ Hui-ping; YE Gong-yin; XU Yin; HU Cui; YAO Peng-cheng (浙江大学学报. 农业与生命科学版, 2003)
The ultrastructures of fat bodies before and during vitellogenesis and of follicles at different developmental stages in the parasitoid Pteromalus puparum were studied by electron microscope. At previtellogenic stage (that is, at pupal stage), large amounts of protein granules and mitochondria were present in fat body cells, but no rough endoplasmic reticulum (RER) could be observed. However, there were large amounts of RER as well as mitochondria in fat body cells, and large lipid droplets also occurred during vitellogenesis (that is, the period from pharate adult stage to 5 d after emergence). In the newly formed follicles, there were lots of lipid droplets but no yolk granules in the oocyte. In the grade Ⅰ and grade Ⅱ follicles, lots of yolk granules accumulated in oocytes besides the lipid droplets. In addition, yolk granules in grade Ⅱ follicles were obviously larger than those in grade I follicles. In the grade Ⅲ follices, oocytes were filled with yolk granules and lipid droplets, and eggshells had been formed.